Evidence of a diurnal thermogenic handicap in obesity. (March 2015) - Grimaldi, Daniela; Provini, Federica; Pierangeli, Giulia; Mazzella, Natalia; Zamboni, Giovanni; Marchesini, Giulio; Cortelli, Pietro
Abstract : A thermogenic handicap has been proposed as potential contributor to weight gain in obese subjects but results from clinical studies are inconclusive. We tested whether diurnal and nocturnal body core temperature (BcT) measured for 20-h differed in nine obese subjects compared with 12 lean healthy controls when studied at rest under strictly controlled conditions. BcT was significantly reduced (∼0.35 °C) in obese subjects only during diurnal hours while during nocturnal hours BcT pattern was identical in the two groups. Our preliminary data indicate that obesity is associated with a diurnal thermogenic handicap which could play a role in favoring weight gain by lowering whole-body energy expenditure.